Development and Validation of the Teen Dating Aggression Measure Among Canadian Youth - Persram, Ryan J.; Wong, Tracy K. Y.; Vargas-Madriz, Luis Francisco; Konishi, Chiaki; Dryburgh, Nicole S. J.; Dirks, Melanie A.; Martin-Storey, Alexa; Craig, Wendy (Frontiers in Psychology, 2021)
Teen dating violence (TDV) victimization is a traumatic experience that can have adverse consequences for adolescents. Current measures that assess TDV do not fully distinguish between psychological and relational forms of aggression, nor do they capture aggressive acts that are common within adolescent relationships. The purpose of this study was to evaluate the psychometric properties of the Teen Dating Aggression Measure (TeDAM) using a sample of 730 Canadian adolescents (M = 15.88 years, SD = 1.23). The measure is an expansion of the Conflict in Adolescent Dating Relationships Inventory and includes items that describe other forms of violence such as coercion and control, along with more traditional indicators of dating violence (e.g., sexual aggression). Factor analyses yielded three factors, namely psychological aggression, sexual and physical aggression, and relational aggression, which were correlated with more frequent cannabis and alcohol use as well as rape myth acceptance. These results provide initial support for the utility of the TeDAM for assessing TDV with adolescents.